PRELIMINARY STUDY ANALISIS BEBAN KERJA MENTAL DI INDUSTRI KREATIF - Muhammad Ragil Suryoputro; Retno Gumilar; Nashtiti Aliafari (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
This research was the preliminary study analysis for the mental workload for creative industries. There were issues of productivity during the work performed by the employee. This paper aimed to measure the mental workload based on three job positions for two batik creative industries. The method that used is NASA-TLX, which involved 6 employees. There are variations based on three job positions (production, administrative and packaging) in both industries. The mental workload obtained during the research is 41.67 for UKM Batik 1 and 70.44 for UKM Batik 2. In overall, both batik industries having high mental workload, only in small portion is in medium position. The highest mental workload was for production process in UKM Batik 2. The further research should be conducted on improving the work system design for all positions, especially on production process.